2013
DOI: 10.1128/aem.02733-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Quantitative Analysis of Gene Expression Profiles of Glycoside Hydrolase Family 10 Xylanases in the Sheep Rumen during a Feeding Cycle

Abstract: Xylanase is a crucial hydrolytic enzyme that degrades plant polysaccharides in the rumen. To date, there is no information on the genetic composition and expression characteristics of ruminal xylanase during feeding cycles of ruminants. Here, the major xylanase of the glycoside hydrolase family 10 (GH 10) from the rumen of small-tail Han sheep was investigated during a feeding cycle. We identified 44 distinct GH 10 xylanase gene fragments at both the genomic and transcriptional levels. Comparison of their rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Because xylan degradation by xylanase is the first step taken to break down the lignocellulose in feedstuff, a xylanase with high catalytic performance is more favorable for feedstuff utilization. In our previous study of xylanase expression in sheep rumen, xynA was found to represent the most predominantly expressed xylanase gene of GH10 (15). We conjecture that XynA has certain favorable characteristics over others in the highly competitive rumen environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because xylan degradation by xylanase is the first step taken to break down the lignocellulose in feedstuff, a xylanase with high catalytic performance is more favorable for feedstuff utilization. In our previous study of xylanase expression in sheep rumen, xynA was found to represent the most predominantly expressed xylanase gene of GH10 (15). We conjecture that XynA has certain favorable characteristics over others in the highly competitive rumen environment.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (36) fused an oligopeptide to the N terminus of an ␣-amylase and improved its catalytic efficiency, thermal stability, and resistance to oxidation. In this study, we fused the proline-rich sequence of XynA to the C terminus of another ruminal xylanase (XynB) of the same source and the same family (15). The fused protein showed an improved catalytic efficiency of 27-fold and more complete hydrolysis products, mainly xylose and xylobiose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study has shown that, during a 24‐h feeding cycle, the bacterial population in sheep rumen fluid kept increasing, reached the maximum at 12 h and then decreased in the next 12 h slowly (Li et al . ). In this changing environment, ruminal microbes are likely to produce functional enzymes with different pH preferences.…”
Section: Introductionmentioning
confidence: 97%
“…They found 32 genera that were common in all samples but exhibit high variability in abundance across samples. In another approach, Li et al ( 2013 ) studied the expression profi le of the major xylanase of the glycoside hydrolase family 10 (GH 10) from the rumen samples at the time of feeding cycles of a small-tail Han sheep. Evidence of the presence of 44 distinct GH 10 xylanase gene fragments at both the genomic and transcriptional levels was found.…”
Section: Introductionmentioning
confidence: 99%